2010
DOI: 10.1002/lapl.201010045
|View full text |Cite
|
Sign up to set email alerts
|

All-solid-state Nd:LuVO4 laser operating at 1066 nm and 1343 nm under diode pumping into the emitting level

Abstract: We report a high-efficiency Nd:LuVO 4 laser operating at 1066 and 1343 nm, respectively, direct pumped by a diode laser at 880 nm. The maximum outputs of 10.5 and 7.0 W, at 1066 and 1343 nm, respectively, are obtained in a 8-mm-thick 0.4 at.% Nd:LuVO4 crystal with 16.9 W of absorbed pump power at 880 nm, leading to a high slope efficiency with respect to the absorbed pump power of 64.4 and 44.5%. Under traditional pumping at 809 nm, the maximum outputs of 9.8 and 6.2 W, at 1066 and 1343 nm respectively, are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…2 composite crystal the output powers turn to be saturate at high pump powers, nevertheless at these times the laser crystal still has not any damage. The maximum output power obtained in our experiment is about 1.4 -1.6 times higher than those obtained previously in conventional non-composite Nd:LuVO 4 crystals (the maximum CW output power for 0.9 at.% Nd:LuVO 4 crystal is 12.55 W [11], and for 0.4 at.% Nd:LuVO 4 crystal is 10.5 W [12]). M. Tsunekane [6] found that temperature rise in composite Nd:YVO 4 /YVO 4 crystal was reduced to 70% when compared to non-composite one.…”
Section: Resultscontrasting
confidence: 66%
See 3 more Smart Citations
“…2 composite crystal the output powers turn to be saturate at high pump powers, nevertheless at these times the laser crystal still has not any damage. The maximum output power obtained in our experiment is about 1.4 -1.6 times higher than those obtained previously in conventional non-composite Nd:LuVO 4 crystals (the maximum CW output power for 0.9 at.% Nd:LuVO 4 crystal is 12.55 W [11], and for 0.4 at.% Nd:LuVO 4 crystal is 10.5 W [12]). M. Tsunekane [6] found that temperature rise in composite Nd:YVO 4 /YVO 4 crystal was reduced to 70% when compared to non-composite one.…”
Section: Resultscontrasting
confidence: 66%
“…Our experiments has shown that comparing with single-end bonding Nd:LuVO 4 crystal, double-end bonding style is more effective to relief the thermal loading and can scale laser output to a high power of 17.2 W without saturation. Such value is ∼ 60% higher than the maximum output powers ever obtained previously in conventional non-composite Nd:LuVO 4 crystals with similar doping level [12]. Combining other effective methods that can reduce thermal effect, such as direct pumping with 880 or 915 nm LD [4,8,9,12,41,42], double-end-pumping [9,[43][44][45][46], and further optimization of experimental parameters, we believe that the output power of composite Nd:LuVO 4 crystal can be elevated to the level of composite Nd:YVO 4 and Nd:GdVO 4 , and high power applications of Nd:LuVO 4 crystal will be pushed forward.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Moreover, the method of quasi phase matching (QPM) has made it a promising material for the second harmonic generation (SHG) and optical parametric oscillation (OPO) using the d 33 coefficient [4,5]. Nd-doped crystals, such as Nd:YAG, Nd:YVO 4 , and Nd:LuVO 4 have recently attracted much attention due to their possible utilization as efficient diode pumped solid state lasers [6][7][8][9][10][11]. The LD pumped laser selffrequency-doubling performance have been realized in Nd:YVO 4 /BiBO and Nd:GdVO 4 /LBO crystals [12,13].…”
Section: Introductionmentioning
confidence: 99%